Design and Functionality of a Prototype for Cold Needle Perforation of Wheat - Luca Stäheli; Lisa Schwab; Mathias Kinner; Nadina Müller (Applied Sciences, 2023)
Wheat is a vital crop in global food security, but up to 25% of the wheat harvested is contaminated with mycotoxins that have detrimental effects on human health. To address this issue, biological detoxification strategies have been developed using microorganisms and enzymes. Perforating the whole wheat kernel using cold needle perforation (CNP) followed by a detoxification step could be a promising approach to reduce cross-contamination during the milling of mycotoxin-containing wheat. In this study, a pilot-scale CNP prototype was developed to perforate wheat kernels, and its effectiveness was evaluated. The height-adjustable perforation unit consists of 3120 needles. The throughput of the CNP prototype was adjusted to 6 kg/h, and the kernels were perforated for 1, 5, or 10 cycles. The results show that the CNP prototype effectively perforates wheat kernels, as evidenced by the significant increase in pore count. Fluorescence microscopy confirmed the penetration of particles in the size range of enzymes and microorganisms into the kernel. This study demonstrates the successful scale-up of CNP for wheat kernel perforation and highlights the potential of CNP as a cost-effective and efficient method for the biological detoxification of mycotoxin-contaminated wheat.